Are public private partnerships effective in delivering public office accomodation projects? - Bogopane, Oarona (My University, 2008)
The key question this thesis investigates is whether Public Private Partnerships (PPPs) are relevant and effective in delivering office accommodation projects in South Africa. While the procurement of large infrastructure projects in South Africa. is currently dominated by PPPs, it is, however, a relatively new form of procurement and presents a steep learning curve for those participating in such projects as they evolve. As South African PPPs are modelled on UK experiences of such partnerships, the greatest challenge we face is to adapt the model so that it recognizes and incorporates the unique South African context within which we work. Furthermore, while PPPs have been applied to a number of building-related infrastructure projects, they have only recently been applied to office accommodation ones. We thus need to explore and apply the relevant aspect of the PPP model for this particular type of accommodation. The South African National Treasury’s list of PPP projects planned for the coming years shows there is a high demand from national and local government departments for office accommodation, as well as a significant backlog for such facilities. This is placing considerable pressure not only on the delivery of such facilities, but also on the ability of government to finance the projects with funds required for other core government obligations. Government has thus had to adopt an alternative means of addressing these issues and is now engaging the private sector to provide the facilities, the financing and the services related to such accommodation. Using a detailed survey and a study of the relevant literature, this report highlights the key aspects to be taken into consideration in determining the relevance of PPPs in the effective delivery of office accommodation and makes useful recommendations based on the outcomes of the study.